Gröna tak som del i ett hållbart stadsbyggande - Blomberg, Anders (2009)
Green roofs have seen a revival in the society of today. They provide many functions of which both society as a whole and the individual can take part. In particular extensive green roofs, that requires little or even zero maintenance, provides very valuable functions. Green roofs affect our environment and our economy in a positive manner as well as the physical expression of buildings. In this bachelor thesis the impact of green roofs on society has been examined throughout literature studies. The result as a compilation of contemporary research in this field is presented together with a discussion about the use of green roofs in general. The two major arguments for an extended use of green roofs are, the high stormwater retention capacity and the cost-benefits seen over time compared to a conventional roof. Green roofs can hold and delay major amounts of stormwater. Furthermore the costs for a conventional roof, over time, are seen to be as high or even higher than those of a green roof. Additionally, green roofs contribute to a greater biodiversity in cities, better sound isolation of buildings as well as cleaner air. Since results from different reports differentiate somewhat, more research in the field is preferred.